Pirates & patriots, tales of the Delaware coast - Morgan, Michael, 1943- (Algora Pub., 2005)
Piecing together clues found in regional archives, libraries and museums, author Michael Morgan presents the colorful characters who line the history of Delaware from its earliest colonial days to the invention of the "beach resort" and the founding of the nation's "Summer Capital" to World War II and the present. He brings together a kaleidoscopic view of the men of the sea and the beachfront tycoons who shaped Delaware and its role in the development of America, in war, politics, and business, from the Europeans' arrival at Cape Henlopen until modern times. While the intrepid patriot Henry Fisher and the infamous serial killer Patty Cannon may not be known beyond the boundaries of southern Delaware, others such as William Penn, Captain Kidd and the DuPonts enjoy more widespread renown. Here, tales of shipwrecks and rumrunners combine with the politics of slavery and suffrage to illuminate the history of one corner of the United States, a microcosm that sheds light on various facets of the development of the nation in a broader context. Michael Morgan pens a weekly column, "Delaware Diary," for the Delaware Coast Press and has authored many stories for The Baltimore Sun, Maryland Magazine, Civil War Times Illustrated, America's Civil War and other periodicals for the past 15 years. He is a frequent guest speaker at historical societies in Lewes, Georgetown, and other towns along the Delaware coast.